ANALISIS PENYEBARAN POHON MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KELOMPOK HUTAN PRODUKSI DUSUN V KEBUN KOPI DESA NUPABOMBA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Aryawan, I Made Suke; Zain, Akhbar; Arianingsih, Ida (Universitas Tadulako, 2014)
The aim of this research was to know distribution of the trees in production forest group, Nupabomba village, Tanantovea district, Donggala regency. Using Geography Information System (GIS), we determine tree distribution in three slope class (0-8%, 8-15% and 15-25%).The period of study was from June to August 2013.Studywasdone bysome steps, i.e; mapping of research location, plotting, tree distribution data collection and analysis, and tree distribution mapping.The result showed that in the east part of the slope, the total number of plant species recorded in the slope class 0-8% was 39 individual trees comprising 10 species and 23 families, in the slope class 8-15% was 24 individual trees comprising 8 species and 7 families, and in the slope class 15-25% was 20 individual trees comprising 8 species and 7 families. In the west part, the total number of plant species recorded in the slope class 0-8% was 31individual trees comprising 9 species and 9 families, in the slope class 8-15% was 25 individual trees comprising 10 species and 9 families, and in the slope class 15-25% was 19 individual trees comprising 8 species and 8 families. It was concluded that there were 78 and 75 individual trees in east and west part of slope, respectively. Hence, the total number of the tree in the slope class 0-8% was higher than two other slope class. Keywords: Tree distribution, Geography System Information, Production Forest.